The Feeling of Surrender: Patients’ Perceptions of their Interactions with Nurses - Sukriyadi (Indian Journal of Public Health Research & Development, 2019)
Background Meaningful nurse-patient interaction is crucial to achieving better health outcomes. A nurse should understand the importance of tailored effective communication to understanding how each patient prefers to be treated. Nurse-patient interaction is a potential resource to promote hope, meaning and purpose in life, which results in harmony and healing environment. Previous studies have shown a variety of aspects of nurse-patient interaction, however the process of interaction have not been thoroughly investigated from the patients’ viewpoint. This qualitative study aimed to investigate patients’ perceptions of their interactions with nurses in the hospital wards. Method A phenomenological approach was undertaken in one public hospital in Indonesia. 10 participants were recruited from general wards by purposeful sampling method. The data were collected through observations of nurse-patient interaction, the ward atmosphere as well as the activities by semi-structured interviews. Transcripts were then examined and analyzed by Interpretive Phenomenological Analysis (IPA) approach. Result Three themes were extracted from data analysis including saying sorry for neglecting me, calming the atmosphere for nurses’ openness and feeling surrender to destiny. Discussion and Conclusion Based on the results, issues such nurses’ openness and positive atmosphere in the hospital wards are shown to be important in maintaining the best quality of nurse-patient interactions. Nurses should be aware of these factors during interactions with patients